Study of frequency-controlled asynchronous motor units temperature versus load and power supply type - T.V. Vakaruk (National Technical University "Kharkiv Polytechnic Institute", 2014)
An equivalent thermal circuit is developed to form the basis of a system of heat-balance equations for a frequency-controlled induction motor. With the system of equations, temperatures of АИР 90В2 induction motor stator and rotor windings and cores are calculated and experimentally confirmed. The load dependence of the machine most heated units temperature at different forms of the supply voltage is revealed.